Cholesterol and Malondialdehyde Contents of Broiler-Chicken Meat Supplemented with Indigofera zolingeriana Top Leaf Meal - M. A. Santi; . Sumiati; L. Abdullah (Media Peternakan, 2015)
This research aimed to increase functional value of broiler-chicken meat containing high antioxidant and low cholesterol through substitution of soybean meal (SBM) with Indigofera zollingeriana top leaf meal (ILM). The experiment used 160 day old broiler chicken (Cobb strain). The experimental chicken were provided dietary treatments when they were 15-days old (initial body weight of 460.5±1.56 g/bird) and terminated on day 35. A completely randomized design (CRD) with four treatments and four replications and ten birds in each replication was used in this experiment. Dietary treatments were: R1= diet containing 20% soybean meal (SBM) without I. zollingeriana top leaf meal (ILM); R2= diet containing 16% SBM and 5.9% ILM; R3= diet containing 12% SBM and 11.8% ILM; R4= diet containing 8% SBM and 17.74% ILM. Variables measured were performances (feed consumption, body weight gain, and feed conversion) and the quality of broiler meat (cholesterol, fat content, and malondialdehyde [MDA] concentration). The results showed that supplementation of 17.74%  ILM (R4) as the substitution of 60% soybean meal protein produced the same performances of broilers as those of control diet (R1). Supplementation of 11.8% ILM as the substitution of 40% soybean meal protein (R3) decreased meat cholesterol by 34.70%, meat fat content by 52.93%, and MDA concentration by 62.52%. The conclusion of this study was that supplementation of 17.74% ILM produced the same performances as that of control diet, increased antioxidant content of the meat, indicated by a lower MDA concentration, and decreased cholesterol, as well as fat content of broiler-chicken meat.Key words: broiler performance, cholesterol, Indigofera zollingeriana, malondialdehyde (MDA)